KAJIAN PEMANFAATAN MACHINING CENTER OLEH INDUSTRI KECIL DAN MENENGAH (IKM) LOGAM DI YOGYAKARTA - , WILDANUL ISNAINI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Machining center has been developed in several countries, for example is China, Taiwan, and the USA. Machining center is a machining process of material with computer numerical and control axis that use a lot of various types of equipment and operation (Ryerson, 2003). Machining centers are already developed in several countries is a combination of CNC EDM, ECM, or USM. In Indonesia, the development of technologies such as machining centers is still said to be minimal. In fact, the government of Indonesia through Bappenas (2013), is in an effort to enhance the technological capabilities in small industrial enterprises as well as develop an integrated manner the dominant sector of small industries. To support that government program appeared an idea to develop the machining center which has addpted in some countries this at Industri Kecil dan Menengah (IKM) in Indonesia. This study begins with the retrieval of data in 32 IKMs in Yogyakarta. The results of data collection are used to determine the map technology IKMs in Yogyakarta as well as to determine which of IKMs will be used as the object of research. The method used in this study were simulated with the help of software ProModel. Simulation was conducted to determine the efficiency of production processes in IKMs as well as an increase in productivity after implementation of machining centers. Then calculate the economic feasibility analysis of the application of machining centers in IKMs such as Pay Back Period, Net Present Value and Internal Rate of Return. From 18 metalâs IKM, machining process that most used are drilling machines, grinding machines, and lathes, while the highest number of combinations of the machining process used is 3, is by 44%. That three combination consist of lathe, drill, and grinding. The concept of machining center offerings for IKM ED Aluminum consists of six process, there are polishing and lathe. Sixth machining process is incorporated in the machining center that is integrated with the computer. The results of the simulation machining center in the IKM ED Aluminium provide additional production capacity that is 51% for wajan biasa type, 88% for wajan dinar type, and 91% for wajan cincin 2 12 type. Based on the economic feasibility, the application of machining centers in the IKM ED Aluminium is feasible to applicate with PBP in 4.51 years, NPV of Rp 259.561.824, and an IRR of 13%.